KOMUNIKASI INSTRUKSIONAL GURU PADA KELAS KHUSUS DI SMK LABOR BINAAN FKIP UNIVERSITAS RIAU (STUDI PADA PROGRAM KEAHLIAN TEKNIK KOMPUTER DAN JARINGAN) - Ariska, Lisa; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Every teacher has hope for improvement of student's learning achievement. Therefore, teachers use instructional communication in order to change student behavior to be a better direction. Instructional communication is an interaction used by teachers in the learning process to improve student achievement in Computer and Engineering skills programs network. The purpose of this research is to know the instructional communication process, methods and instructional media that teachers use when teaching productive subjects.This research uses qualitative research method. Informers at this research are the head of program expertise, teachers, and students on the Computer Network Engineering expertise program. While the object in this study is instructional communication of teachers on Computer Engineering and programming skills Network at Vocational High School Teachers Training Faculty of Labor University of Riau. Data collection techniques used are observation, interview and documentation. In achieving the validity of data in this study, the authors used extension of participation and triangulation.The results showed that instructional instructional process of teacher who taught productive subjects on Computer Engineering programming skills and Network includes content specifications and instructional objectives, early behavioral assessment, the establishment of instructional strategies, the organization of instructional units, and feedback. Instructional communication is done using method lectures, discussions, demonstrations, field trips, experiments, exercises, and problems solving. To support instructional communication to run smoothly, then media of learning are required. The media used by teachers are books, computers, pictures, modules, internet, e-learning, applications, video, projectors, and other tools students need when practicing like utp cable, crimping tool, lan tester, rj45 connector, wireless card, hub, router, switch, cd installation, screwdrivers plus minus, pliers, brushes.Keywords: Instructional Communication, Vocational High School, Engineering Computers and Networks